Clinical presentation, investigation findings, and treatment outcomes of intraluminal small intestinal obstruction by bezoars and other materials in adult cows– a retrospective study of 110 cases - Ueli Braun; Christian Gerspach; Elena Bennien; Monika Hilbe; Karl Nuss (BMC Veterinary Research)
Abstract Background Small intestinal obstruction (SIO) is a blockage of the intestinal lumen by blunt foreign bodies, neoplasms originating from the intestinal wall or thick chyme. This study analysed the medical records (only data) of 110 cattle with SIO and described the clinical findings, treatment and outcome. These findings were compared between surviving and non-surviving cattle, and among the affected regions such as the duodenum, jejunum and ileum. Results Colic occurred in 42.7% (47/110) of the cattle. Rumen motility was absent in all cattle and intestinal motility was reduced or absent in 82.6% (90/109). Ballottement and/or percussion and simultaneous auscultation were positive on the right side in 63.3% (69/109). Little or no faeces in the rectum occurred in 93.6% (102/109) of the cattle. Dilated loops of small intestines could be palpated transrectally in 46.8% (51/109) and the actual obstruction (palpated as a firm mass in the small intestine) in 5.5% (6/109) of the cattle. The main laboratory changes were hypokalaemia (80.9%, 89/110), hypermagnesaemia (75.3% 58/77), hypocalcaemia (71.8%, 56/78), haemoconcentration (66.4%, 73/110), azotaemia (66.4%, 73/110) and positive base excess (63.3%, 62/98). Abnormal ultrasonographic findings included dilated loops of small intestines (94.3%, 83/88) and subjectively reduced or absent small intestinal motility (85.4%, 70/82). The actual obstruction could be visualised in 3.4% (3/89) of the cattle by ultrasonography. In the 14 non-surviving and the 96 surviving cattle the frequencies of abdominal dilatation (57.1%, 8/14 vs. 22.1%, 21/95) and the presence of blood, mucus and/or fibrin in the rectum (92.9%, 13/14 vs. 63.2%, 60/95) were significantly different. Abomasal reflux syndrome was significantly worse in the cattle with duodenal obstruction (26/110) than in those with jejunal (51/110) or ileal obstruction (33/110). A total of 107 cattle underwent right flank laparotomy, and the obstruction was resolved by massaging the affected area or it was removed via enterotomy. Of the 110 cattle, 14 (12.7%) were euthanized and 96 (87.3%) were discharged 3 to 10 days after surgery. Conclusions Transrectal and/or ultrasonographic diagnosis is the exception, and in almost all cases laparotomy, was required. The prognosis is good provided that surgical treatment is carried out promptly.